1996
DOI: 10.1007/bf02278258
|View full text |Cite
|
Sign up to set email alerts
|

The utility estimate as a communication device: Practical questions and research directions

Abstract: ABSTRACT" Rauschenberger and Schmidt (1987) lamented the lack of research attention to the ways in which utility information is presented to organizational decision makers. However, while considerable research has continued to focus on technical issues surrounding utility estimation, few studies have specifically examined the efficacy of the utility estimate as a communication device. The purpose of this article is to set forth an agenda for future research on the communication of the value of human resource a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The higher acceptance of causal chain analysis fits in nicely with the finding of Hazer and Highhouse (1997), who argued that the Cascio‐Ramos estimate of performance in dollars (CREPID) methodology to determine SD y is particularly difficult to explain and understand (Highhouse, 1996). This argument was supported by their finding that the CREPID methodology of determining SD y yielded the least favorable reactions.…”
Section: Discussionsupporting
confidence: 53%
“…The higher acceptance of causal chain analysis fits in nicely with the finding of Hazer and Highhouse (1997), who argued that the Cascio‐Ramos estimate of performance in dollars (CREPID) methodology to determine SD y is particularly difficult to explain and understand (Highhouse, 1996). This argument was supported by their finding that the CREPID methodology of determining SD y yielded the least favorable reactions.…”
Section: Discussionsupporting
confidence: 53%
“…Another fruitful direction for future research consists in framing the provision of pre-test information into broader models of social persuasion, belief change, and attitude change (e.g., Carson et al 1998;Highhouse 1996;Morley 1987;Petty and Cacioppo 1981). This social psychology literature on persuasion might be useful to construct ideal methods of presenting pre-test information to applicants.…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…Persuasive communication research may shed light on this issue (Highhouse, 1996). Petty and Cacioppo (1986) suggested that when selling an argument, one should decrease the level of complexity in the message.…”
Section: Presentation Of Ua Informationmentioning
confidence: 99%